Effectiveness of Archive Management at the Regional Office of the Ministry of Law and Human Rights of South Sulawesi - Musba, Musba; Jamaluddin, Jamaluddin; Nasrullah, Muh (Pendidikan Administrasi Perkantoran, UNM, 2025)
Good archive management can help increase productivity and work efficiency because it allows quick access to the necessary information. The goal of archive management is to make it easier to use in the future. Human resources for archive management, also called archival personnel, are an important component in archive management. They must work hard to manage the growing number of archives so they don't pile up. This study aims to determine the Effectiveness of Archives Management in the Regional Office of the Ministry of Law and Human Rights of South Sulawesi. This study uses a qualitative approach with a descriptive type of research. The informants in this study consisted of the Head of the Personnel Sub-Division and the Personnel Administration Staff at the Regional Office of the Ministry of Law and Human Rights of South Sulawesi. The data collection techniques employed in this study include observation, interviews, and documentation methods. The data analysis techniques used are data condensation techniques, data presentation, and conclusions drawn. The results of the study show that the management of archives at the regional office of the Ministry of Law and Human Rights in South Sulawesi is categorised as ineffective. Numerous factors and indicators characterise archive management. The creation of archives is good because employees have created them appropriately; they make documents in accordance with the procedures for making letters that have been set. The use of archives is still not optimal due to inadequate storage facilities, such as storage rooms and equipment and the lack of trained human resources in archive management. Archive maintenance is still very limited because there are no special facilities to store archives and maintain their security. Archive shrinkage has not been maximised due to a limited understanding of procedures and a lack of archival experts, so it is carried out independently without adequate guidance.